Epidemiological Situation of Measles in One of the Regions of the Republic of Kazakhstan - Omarova, Alua Oralovna (Asian Journal of Pharmaceutics (AJP), 2017)
Objective: The aim of this study is to assessthe epidemiological situation of measles in one of the regions of the Republic of Kazakhstan. Materials and Methods: Retrospective study of measles morbidity during 2004-2014 was conducted. Statistical processing was carried out on the basis of the applied program of statistical processing â€œIBM SPSS Statistics 20.â€ Results: The peak of incidence in one of the regions of Republic was registered in 2005, and by 2006, there has been a decrease in 81.1 times. Compared with the preceding year in 2014 there is an increase of incidence of measles in 1.1 times. Adults are sick with measles more often than children under 14. Until 2012, measles had often been registered among city dwellers; in 2013 and 2014, an increase of incidence of people who live in the country was noted. Index of timeliness of vaccination coverage against measles corresponded to normative indexes among babies under 1-year-old. A credible strong inverse correlation between measles morbidity and vaccination coverage ratio was found. Conclusion: The epidemiological situation of measles in the region remains tense.